Influence of Lanthanide Promoters on Ni/SBA-15 Catalysts for Syngas Production by Methane Dry Reforming - Omoregbe, Osaze; Danh, Huong T.; Abidin, S. Z.; Setiabudi, H. D.; Bawadi, Abdullah; Vu, Khanh B.; Vo, Dai-Viet N. (Elsevier Ltd, 2016)
The catalytic performance of Ce- and La-promoted Ni/SBA-15 catalysts for syngas production from CO2 reforming of methane has been investigated in a fixed-bed reactor at stoichiometric feed composition. Both promoted and unpromoted catalysts possessed high BET surface area of 303-445 m2 g-1. Additionally, SBA-15 support had a relatively uniform rod-like shape with a diameter of about 0.55 μm and a reduction in the crystallite size of NiO phase from 27.0 to 19.1 nm was observed with promoter addition reasonably due to the strong interaction between promoter and NiO particles. CeO2 and La2O3 dopants were finely dispersed on catalyst surface. Temperature-programmed oxidation of spent catalysts showed that coke-resistance was improved significantly with promoter modification and 3%La-10%Ni/SBA-15 catalyst was the most resistant to carbonaceous deposition rationally due to the least NiO crystallite size hindering the nucleation and growth of graphitic carbon. Hence, La-promoted catalyst appeared to be the optimum catalyst in terms of reactant conversion, H2 yield and stability whilst a gradual decline in both reactant conversion and H2 yield was experienced with unpromoted and Ce-doped catalysts. Regardless of catalyst types, the ratio of H2 to CO was always less than unity preferred for Fischer-Tropsch synthesis.